Magnetic and Dyed Microcapsules From the Spores of Clubmoss - Cai, Wen; Bradbury, Charles; Cowling, Stephen; Goodby, John (Frontiers in Physics, 2022)
In this article we describe the preparation of bioavailable microcapsules derived from spores of clubmoss (Lycopodium clavatum) that are composed of protein-free, non-allergenic, and porous sporopollenin, often described as nature’s most robust polymeric system. We describe the adsorption of magnetic materials onto the exterior surfaces of the empty microcapsules and the incorporation of molecular passengers , thereby producing stable , monodispersed, bifunctional particles/vehicles of 25 microns in size that can respond to, or targeted by, applied fields.